A Case Control Study to Elucidate Maternal Determinants of Intra Uterine Growth Retardation in A Tertiary Care Hospital of Sagar City Of Madhya Pradesh - Pandey , Shikha; Pandey , Ramesh (National Journal of Community Medicine, 2012)
Objectives: To study the maternal determinants of intrauterine growth retardation among cases admitted for delivery in Bundelkhand Medical College, Sagar. Methods: A Case-control study was conducted in the year January 2010 to December 2010 in Bundelkhand Medical College (BMC) Sagar M.P. The participants included mothers who underwent normal delivery in BMC Sagar. Mother's age, parity, maternal height, maternal weight, body mass index, hemoglobin level during pregnancy, birth weight of the baby were considered as study variables. Intrauterine growth retardation was taken as outcome variable. Chi square test. OR's with 95% CI was used as the method of statistical analysis. Results: Significant risk factors identified in univariate analysis included maternal height (<145 cm s.), maternal weight (<45 kg s.), body mass index (<18.5) and anemia in pregnancy. Multiple logistic regression analysis revealed that maternal age (>30 years), primiparity, maternal height (<145cms.) maternal weight (<45 kg s.), anemia in pregnancy (Hb <11gm %) is the significant risk factors of intrauterine growth retardation.